Evaluation of the Amplicor Chlamydia trachomatis test versus culture in genital samples in various prevalence populations. Issue 3 (June 1994) - de Barbeyrac, B; Pellet, I; Dutilh, B; Bébéar, C; Dumon, B; Géniaux, M; Bébéar, C
Abstract : OBJECTIVE–To evaluate a newly developed polymerase chain reaction (PCR) assay, Amplicor C trachomatis for the detection of C trachomatis in genital samples using cell culture for comparison. SUBJECTS–501 patients (431 women and 70 men) attending an STD clinic in Hôpital Pellegrin (high-risk population) and gynaecological clinics (low-risk population) in Bordeaux, France. METHODS–The genital samples (cervical and urethral) were tested for the presence of C trachomatis using the Amplicor test and using standard cell culture identified by the immunofluorescence test using a monoclonal antibody to C trachomatis. Discrepancies between the results of culture and Amplicor were further analysed by major outer membrane protein gene (omp1)-PCR of the specimens taken in transport media and by direct fluorescent antibody (DFA) staining of elementary bodies in culture transport tubes. RESULTS–After analysis of discrepancies, the revised sensitivity and specificity of PCR were 95.3% and 100% and the positive and negative predictive values were 100% and 99.5%, respectively. CONCLUSION–The present results indicate that the Amplicor assay is rapid, specific and more sensitive than the culture method. This test provides an excellent non-culture method for the detection of C trachomatis in various prevalence populations.